1995
DOI: 10.1071/rd9950499
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress--the key to parturition?

Abstract: It is clear that the timing of parturition is dependent on a cascade of endocrine signals from an intact fetal hypothalamo-pituitary-adrenal axis. What is not known, however is the nature or source of the central neural stimulation which results in the stimulation of adrenocorticotrophic hormone (ACTH) synthesis and secretion in late gestation. The changes which occur in the synthesis and posttranslational processing of the ACTH precursor, proopiomelanocortin (POMC), in the fetal anterior pituitary before birt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…McMillen et al (33) also found that fetal plasma ACTH concentrations double between 120 and 136 d and 140 and 143 d gestation. In the current study, fetal plasma ACTH concentrations did not increase in the control group but doubled in the FX group on infusion d 7.…”
Section: Discussionmentioning
confidence: 93%
“…McMillen et al (33) also found that fetal plasma ACTH concentrations double between 120 and 136 d and 140 and 143 d gestation. In the current study, fetal plasma ACTH concentrations did not increase in the control group but doubled in the FX group on infusion d 7.…”
Section: Discussionmentioning
confidence: 93%
“…The maturation of the hypothalamo-pituitary adrenal axis in sheep clearly occurs very early during development, with this axis being functional even before birth (Brooks et al 1992, McMillen et al 1995, Matthews & Challis 1996, Reperant & Durand 1997, Challis et al 2001. Our results show that in both 1 and 8 week old male and female lambs the hypothalamo-pituitary adrenal axis was sufficiently mature to be capable of responding to the stress of tail docking, to treatment with ACTH and, in males, to the combined stress of tail docking and castration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the hypothalamo-pituitary adrenal axis in sheep becomes functional during fetal life (Brooks et al 1992, McMillen et al 1995, Matthews & Challis 1996, Reperant & Durand 1997, Challis et al 2001. A steady increase in circulating concentrations of cortisol towards the end of gestation has an important role in the maturation of the fetal organ systems and in triggering parturition (Matthews & Challis 1996, Reperant & Durand 1997, Challis et al 2001.…”
Section: Introductionmentioning
confidence: 99%
“…However, the short-lasting peak values around expulsion cannot be explained in this way. Maternal and foetal endocrine changes that lead to the onset of labour are well known and have been detailed in many papers (Barragry 1975, Cox 1975, McFeely & Ganjam 1976, Challis et al 1977, Flint et al 1978, Challis & Mitchell 1981, Brooks & Challis 1988, Thorburn et al 1991, Wood & Keller-Wood 1991, McMillen et al 1995. In sheep, an increase in the activity of the foetal hypothalamo-pituitary-adrenal axis initiates parturition (Liggins et al 1977).…”
Section: Figurementioning
confidence: 99%